1979
DOI: 10.1161/01.hyp.1.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreceptor reflex control of sympathetic nerve activity in the spontaneously hypertensive rat.

Abstract: SUMMARY The combined and individual carotid sinus and aortic baroreceptor control of sympathetic nerve activity (SNA) and mean arterial pressure (MAP) were studied by direct measurement In groups of spontaneously hypertensive rats (SHR) and normotensive Kyoto Wistar rats (WKY) of 5 to 40 weeks of age. The SHR showed a significantly greater SNA and resultant MAP increase as a function of age compared to that of the WKY rats. Both SHR and WKY rats showed a significant rise in SNA and MAP with ablation of all fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
4

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 23 publications
8
70
0
4
Order By: Relevance
“…According to Ito et al 22 , although the inhibition of endogenous rho-kinase in the medulla oblongata augments the baroreflex control of heart rate in WKY and SHR, it improves the impaired baroreflex function in SHR. Earlier studies that described a significant difference in blood pressure between WKY and SHR at 3 weeks of age 23 or at birth 24 were based on the assessment of a few animals. However, the age at which the baroreflex function starts to decrease in SHR has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ito et al 22 , although the inhibition of endogenous rho-kinase in the medulla oblongata augments the baroreflex control of heart rate in WKY and SHR, it improves the impaired baroreflex function in SHR. Earlier studies that described a significant difference in blood pressure between WKY and SHR at 3 weeks of age 23 or at birth 24 were based on the assessment of a few animals. However, the age at which the baroreflex function starts to decrease in SHR has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested the important role of the SNS in the spontaneously hypertensive rat (SHR) and the stroke-prone SHR (SHRSP); SHR have been shown to exhibit elevated efferent renal sympathetic nerve activity (RSNA) before hypertension is established (3). In addition, the renal norepinephrine (NE) content has been reported to be 2 times and 1.5 times greater in newborn (4) and adult SHR (5), respectively, when compared with age-and sex-matched Wistar-Kyoto rats (WKY).…”
Section: Introductionmentioning
confidence: 99%
“…6 In rats, the baroreceptor reflex control of heart rate may be enhanced by AVP through V 2 receptors, 22 whereas the pressor activity of AVP may be buffered through a nonbaroreceptor reflex withdrawal of sympathetic tone. 23 Interestingly, sympathetic hyperactivity 24 and impairment of baroreceptor reflex function 25 are found in SHR. Unlike the normotensive dog 26 and rat 27 , in which baroreceptor reflex function improves with age, SHR has an age-dependent impairment of baroreceptor reflex function.…”
Section: Discussionmentioning
confidence: 99%